Drought stress reduces the photosynthetic source of subtending leaves and the transit sink function of podshells, leading to reduced seed weight in soybean plants - Xiangbei Du; Xinyue Zhang; Xiaofei Chen; Wenjun Jin; Zhiping Huang; Lingcong Kong (Frontiers in Plant Science, 2024)
Drought stress is the key factor limiting soybean yield potential. Soybean seed formation involves a coordinated “subtending leaf-podshell-seed” process, but little is known about the assimilation and transport of photoassimilates in subtending leaves, podshells and seeds or their relationships with soybean seed formation under drought stress. To address these research gaps, two-year experiments with two soybean cultivars, Wandou 37 (drought tolerant) and Zhonghuang 13 (drought sensitive), were conducted under three soil water content (SWC) conditions in 2020 and 2021 based on the responses of their yield to drought. We analyzed the photosynthetic assimilation and translocation of photoassimilates in subtending leaves, podshells and seeds by stable isotope labeling. Compared with those under 75% SWC, 60% SWC and 45% SWC significantly decreased the Wandou 37 seed weight by 19.4% and 37.5%, respectively, and that of Zhonghuang 13 by 26.9% and 48.6%, respectively. Compared with those under 75% SWC, drought stress decreased the net photosynthetic rate and the activities of sucrose phosphate synthase (SPS) and sucrose synthase (SuSy), which in turn decreased the photosynthetic capacity of the subtending leaves. The podshells ensure the input of photoassimilates by increasing the SuSy activity, but the weakened source–sink relationship between podshells and seeds under drought stress leads to a decrease in the translocation of assimilates from podshells to seeds. The lack of assimilates under drought stress is an important factor restricting the development of soybean seeds. We conclude that the decrease in seed weight was caused by the decrease in the photosynthetic capacity of the subtending leaves and the decrease in the overall availability of photoassimilates; moreover, by a decrease in the translocation of assimilates from podshells to seeds.